PROBLEMS OF PARENTS CARING FOR CHILDREN WITH DISABILITIES - Lekholetova, Maryna; Liakh, Tetiana; Zaveryko, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The development of integrated social services for parents raising children with disabilities is one of the priorities of social policy in Ukraine. The purpose of this article is to identify the typical problems of parents raising children with disabilities. Based on the in-depth interviews conducted by parents raising children with disabilities in two regions of Ukraine (n=60), groups of typical problems they face (discrimination, medical problems, imperfection of regulatory support, information problems, access problems, problems of early diagnosis / early intervention, psychological problems, risk of institutionalization, financial and economic problems) and their analysis. In-depth interviews identified issues that could provide brief guidance on social work with families raising children with disabilities.The authors draw attention to the urgent and structural changes needed to improve the access of parents of children with disabilities to quality social services and to improve the quality of their social and pedagogical support, including enhancing the educational potential of such parents.